Media Sosial sebagai Ruang Representasi Kehidupan dan Identitas Budaya Pekerja Migran Indonesia - Rachmi Fitria; Amalia Amalia; Siti Zahra; Mirna Nur Alia Abdullah (RESIPROKAL: Jurnal Riset Sosiologi Progresif Aktual, 2026)
The migration of Indonesian Migrant Workers (PMIs) in the digital era is no longer understood merely as labor mobility driven by economic motives, but also as a process of cultural transformation and identity negotiation within transnational spaces. This study aims to analyze how PMIs utilize social media as a space for self-representation, cultural reproduction, and identity negotiation. The study is significant because previous research has mainly focused on social media as a tool for communication, activism, and migrant worker protection, while its role in digital cultural reproduction and identity formation remains underexplored. This research employed a descriptive qualitative approach using literature review, in-depth interviews, and document analysis. Data were collected from February to May 2026 through interviews with three PMIs in Japan and Brunei Darussalam and two domestic workers in Indonesia to compare work cultures and everyday practices. Data credibility was ensured through source triangulation and analyzed thematically. The findings reveal differences in work culture between host countries and Indonesia. PMIs experience tensions between the habitus formed in Indonesia and the work cultures of host countries, which emphasize discipline, individualism, and adherence to formal regulations. Social media functions as a space for cultural reproduction, the preservation of Indonesian cultural identity, and symbolic social mobility through self-branding and social recognition. These findings contribute to digital migration studies by conceptualizing social media as a transnational social space where migrant workers actively construct, maintain, and transform their cultural identities. Practically, the study highlights the role of social media in supporting cultural adaptation and preserving national identity among migrant workers abroad.